Teaching Vocabulary to Indonesian Young CHildren with ADHD - Kinasih, Titah; Rochmawati, Dyah (Universitas PGRI Adi Buana Surabaya, 2020)
The aim of the present study is investigating (1) the current teaching techniques of viralslot teaching English vocabulary for children with Attention Deficit Hyperactivity, and (2) the difficulties faced by the teachers in teaching English vocabulary for children with Attention Deficit Hyperactivity viralslot. This survey research employed oral interviews, questionnaire and observation schemes as instruments for data collection. The result of this study indicates that the current techniques employed flashcards, pictures, songs, storytelling. the use of electronic media were the most preferably common techniques in teaching young learners vocabulary. The techniques were sometimes adapted and combined. The difficulties encountered by the teachers were the students’ extensive native language, being uncooperative, inability to stay focused. This study provides some suggestions for they need to be equipped with the methodology of teaching vocabulary for student with such a learning disability. This disability can lead to difficulties in understanding and using language for communication and interaction. Having adequate knowledge of such methodology brings about the equal chances for such students to earn learning success. The article ends up with implications for practice and future research directions viralslot. Keywords: teaching; vocabulary; students with attention deficit hyperactivity disorder